Soybean Oil Deodorizer Distillate (SODD) as feedstock for esters production: techno-economic-environmental analysis of enzymatic routes - Cansian, Ana Bárbara Moulin (Universidade Federal de São Carlos, 2024)
The constant demand for feasible processes maintaining low environmental indicators has been nonstop in recent decades. In response to these goals, the circular economy has emerged, with one of the pillars of coproduct reuse at all stages of production. In the soybean oil industry context, the refining stage produces a residue with significant potential for applications in a biorefinery, further contributing to the circularity of production and the reduction of costs: the soybean oil deodorizer distillate (SODD). The concentrations of fatty acids and mono-, di-, and triglycerides found in SODD make it an exciting prospect as an appealing candidate for conversion into esters through reactions with alcohols or sugars, producing biodiesel or biosurfactants. For laboratory research to be applicable on an industrial scale, techno-economic-environmental analyses must indicate the process's economic viability and environmental impacts. There are several studies related to the experimental data of biodiesel production. However, they are rarer when using raw materials that do not compete with the food industry. Likewise, research into the production of biosurfactants with this type of raw material is rare. Nevertheless, no studies evaluate processes from techno-economic-environmental analysis using SODD. In this context, this work aimed to support the development and scaling of biodiesel (fatty acid ethyl esters) and biosurfactants (fatty acid xylose ester) production by conducting a techno-economic and environmental assessment of enzymatic processes using a subproduct/ residue from biorefineries (SODD) as a material source of fatty acids. Initially, the study focused on the esterification of oleic acid with xylose using immobilized lipase, analyzing economic and environmental factors. Using tert-butanol as a solvent, the Minimum Biosurfactant Selling Price (MBSP) was US$72.37/kg with 86% purity. When methyl ethyl ketone was used instead, and investment in purification increased, the MBSP rose to US$392.98/kg with 96% purity, suitable for pharmaceutical and cosmetic industries. Additionally, enzymatic biodiesel and biosurfactant production using soybean oil deodorizer distillate (SODD) were modeled. The biodiesel had an MBSP of US$6.15/L and showed lower environmental impacts than traditional method, such as Global Warming Potential in 100 years (GWP100: 1.55 kg CO2 eq.), Abiotic depletion (AD: 27.66 MJ), and Acidification (AC: 3.35∙10^(-3) kg SO2 eq. Three scenarios for biosurfactant production were evaluated, with MBSPs ranging from US$5.82/kg to US$13.42/kg, depending on the solvent mixture. The process with solvent ratio tert-butanol: dimethyl sulfoxide: water of 6.29:1.86:1.86 in volume presented the lowest values of environmental parameters (GWP100: 1.87 kg CO2 eq., AD: 18.4 MJ; AC: 5.09∙10^(-3) kg SO2 eq., EU: 2.54∙10^(-3) kg PO4 eq.). The research concluded that optimizing solvent mixture and using SODD can add value to biorefineries, improving profitability and environmental sustainability.
Destilado da Desodorização do Óleo de Soja (DDOS) como matéria-prima na produção de ésteres: análise técnico-econômica e ambiental de rotas enzimáticas
Keywords: Biossurfactantes; Biodiesel; Modelagem e simulação; Destilado da desodorização do óleo de soja (DDOS); Análise técnico-econômico-ambiental; Biosurfactants; Biodiesel; Modeling and simulation; Soybean oil deodorizer distillate (SODD); Techno-economic-environmental analysis; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA